1990
DOI: 10.1086/168707
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and optical variations in active galactic nuclei - The Seyfert 1 galaxy NGC 5548

Abstract: We describe the results of a project to study the combined ultraviolet-optical spectrum of the Seyfert 1 galaxy NGC 5548 over the period [1978][1979][1980][1981][1982][1983][1984][1985][1986]. Of the many spectrophotometric observations made with a typical resolution of 5-8 Â, 11 epochs were simultaneous and nine cover the range from 1150 to 7000 Â. The combined IUE and ground-based observations, frequently obtained only a few days apart, enable us to study, for the first time, the time variability of many UV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 3 publications
(14 reference statements)
2
64
0
Order By: Relevance
“…Fe II emission is relatively weak in NGC5548 (e.g., Wamsteker et al 1990;Vestergaard & Peterson 2005;Denney et al 2009;Mehdipour et al 2015). Vestergaard & Peterson (2005) selected 73 spectra of NGC5548 spanning 13 yr of the AGN Watch project and quantitatively showed that, on average, the flux ratio of optical Fe II over the range 4250-5710 Å (rest-frame) to broad Hβ line is 0.66.…”
Section: Spectral Measurementsmentioning
confidence: 99%
“…Fe II emission is relatively weak in NGC5548 (e.g., Wamsteker et al 1990;Vestergaard & Peterson 2005;Denney et al 2009;Mehdipour et al 2015). Vestergaard & Peterson (2005) selected 73 spectra of NGC5548 spanning 13 yr of the AGN Watch project and quantitatively showed that, on average, the flux ratio of optical Fe II over the range 4250-5710 Å (rest-frame) to broad Hβ line is 0.66.…”
Section: Spectral Measurementsmentioning
confidence: 99%
“…Especially the large amplitude of the variability offers a good opportunity to evaluate the possible existence of different response characteristics over the extent of the broad lines. The line analysis has been done in three stages following the same procedures as applied by Wamsteker et al (1990) for NGC 5548: first we have removed the various continuum contributions, since especially the small blue bump, mainly composed of Balmer continuum and the many blended FeII lines, form a semicontinuum, which could affect the final results of the line analysis. After the continuum has been properly allowed Fig.…”
Section: Analysis Of the Emission Linesmentioning
confidence: 99%
“…This allows us furthermore to measure strongly blended lines such as Lyαλ1216 and NVλ1240. We have used the error measure of Rodríguez-Pascual (1989) and Wamsteker et al (1990). This method assumes that the component errors are perfectly correlated, and thus gives an upper limit for the error.…”
Section: Line Variability: Total Intensitymentioning
confidence: 99%
See 2 more Smart Citations